Development of an Ethno-STEM Integrated Problem Based Learning Physics E-Module to Improve High School Students' Creative Thinking Skills - Gusdilam Sari; Usmeldi; Desnita; Akmam (Jurnal Penelitian Pendidikan IPA, 2026)
Twenty-first century education demands the cultivation of creative thinking, yet preliminary studies in three high schools in Solok Regency revealed that students' creative thinking skills in physics averaged only 35.5%. This study aims to develop an interactive E-Module of physics on Work and Energy that integrates Problem Based Learning (PBL) with the Etno-STEM approach using the local wisdom of the Minangkabau Rumah Gadang to improve the creative thinking skills of senior high school students. The research employed a Research and Development design using the Plomp model, which consists of three phases: preliminary research, prototyping, and assessment. The product was validated by three experts using Aiken's V; practicality was assessed by teachers (n=2) and students (n=40); and effectiveness was tested through a pretest-posttest control group design at SMA Negeri 1 Pantai Cermin (experimental n=40; control n=41). Results show that the E-Module is highly valid (V = 0.98), highly practical (89.27%), and effective in improving creative thinking skills (N-Gain = 0.66, medium-high category) with significant differences between groups (t = 6.351; p < 0.05) and classical mastery of 87.5%. The integration of PBL and Etno -STEM in a digital, mobile-friendly module proves effective in cultivating fluency, flexibility, originality, and elaboration.